Preventive Significance Of Abhyanga In Dincharya: A Review Article - Dayal, Shambhu; Rani, Seema (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda is a ‘science of life’ which provides not only curative but also preventive principles for healthy and long life. Ayurveda is a life style, a science and an art of appropriate living that ensures health and longevity of human being. Abhyanga (oil massage) which is one among the Dinacharya is also a part of pre therapeutic procedures of Panchakarma. It is an Ayurvedic holistic, synchronized massaging of the body towards the movement of arterial blood, basically in the opposite direction of hair growth. This massage is used for healing and detoxifying the body, mind and spirit. Abhyanga is to be considered in Snehana therapy. As it nourishes the senses of mind and gives the strength. But if done in any region like localised in head, neck, legs etc then it is termed as Shiroabhyanga, Padabhyanga etc. Full body massage gives strength to whole body but localised massage gives strength to that particular part of the body. Abhyanga nourishes; pacifies the doshas; relieves fatigue; provides stamina, pleasure and perfect sleep; enhances the complexion and the lustre of the skin; promotes longevity and nourishes all parts of the body.